Emergency management plan for the unthinkable - Joint Commission Resources, Inc. (Oakbrook Terrace, IL : Joint Commission Resources, 2002)
Describes how to do a hazard vulnerability analysis; discusses the new and existing Joint Commission standards on emergency management; analyzes a disaster preparedness practice drill
Director/producer, Don Hanscom Jr.
VHS
Keywords: Joint Commission on Accreditation of Healthcare Organizations; Emergency Medical Services -- organization & administration; Disaster Planning -- organization & administration